TELAAH KONSEPTUAL TENTANG PROSES SELEKSI DAN PROGRAM ORIENTASI DALAM PENGELOLAAN SUMBER DAYA MANUSIA DI LEMBAGA PENDIDIKAN - Aisyah Rohaniyah; Zahrotin Nur Firda; Najwa Kayla Kamila; Khairun Nasikin; Mardiyah Mardiyah (STKIP Pesisir Selatan, 2025)
The selection process is a crucial part of human resource management, aiming to select prospective employees who align with the organization's values ​​and the position's needs. Selection is the administrative process of accepting or rejecting applicants and ensuring that candidates' abilities meet the job requirements. Therefore, selection is the initial step in determining the quality of the workforce that will support future business performance. Human resources (HR) play an important role in determining the success of an organization. One of the important stages in HR management is selection, which is the process of choosing candidates who are most suitable for the position and organizational values. Selection is not merely an administrative process, but a strategy to produce a competent, competitive workforce that is in line with the culture of the institution. This research uses a library research approach. This paper discusses the concept of selection, sources of selection, types of acceptance tests, various selection challenges, and the importance of HR orientation programs, especially in educational institutions. With a fair and transparent selection system and structured orientation, organizations can develop a professional workforce capable of facing future changes and competition.